The implementation of a deterministic conceptual computer simulation model to characterise the relationship between irrigation return flow and the process of river mineralization - Moolman, J. H.(Joseph Hulme),1950- (Stellenbosch : Stellenbosch University, 2012)
Map in backpocket.